PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Nadila Devianti Putri Maharani; Jacobus Widiatmoko; Kentris Indarti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to examine the effect of disclosure of sustainability reports and intellectual capital on company value with company size, profitability and leverage as control variables. The population in this research are banking companies listed on the Indonesia Stock Exchange in 2018-2022. The data analyzed comes from secondary data taken from annual reports and sustainability reports listed on the Indonesia Stock Exchange. Sample selection was carried out using a purposive sampling technique, so that a sample of 82 data was analyzed. The analytical method used in this research is multiple linear regression. The research results show that disclosure of sustainability reports and intellectual capital have no effect on company value. Testing the control variable for company size has no influence on company value. Meanwhile, profitability and leverage have a positive and significant effect on company value.